All‐Trans Retinoic Acid Ameliorates Arsenic‐Induced Oxidative Stress and Apoptosis in the Rat Uterus by Modulating MAPK Signaling Proteins. Issue 11 (30th May 2017) - Chatterjee, Aniruddha; Chatterji, Urmi
ABSTRACT: Exposure to arsenic leads to inhibition of the anti‐oxidant defense mechanism of the body. Reactive oxygen species generated in response to arsenic causes reproductive failures in exposed females and also acts as an inducer of apoptosis. As a prospective remedial agent, all ‐trans retinoic acid (ATRA) was assessed for reversing arsenic‐induced oxidative stress and apoptosis. Rats exposed to arsenic for 28 days were allowed to recover naturally or were treated simultaneously with ATRA for 28 days or up to 56 days. Production of H2 O2 was detected using 2′, 7′‐dichlorfluorescein diacetate (DCFCA) by flow cytometry. Catalase, superoxide dismutase, glutathione, ALT, and AST were estimated by biochemical assays and Western blot analyses. Detection of apoptosis was performed using annexin V‐FITC/propidium iodide. Expressions of p53, p21, cleaved caspase 3, JNK/pJNK, and ERK/pERK levels were estimated using Western blot analysis. Elemental arsenic deposition in the rat uterus and liver was estimated by atomic absorption spectrophotometry. Our results confirmed that ATRA ameliorated sodium arsenite‐induced ROS generation, restored redox balance, and prevented apoptosis. Concomitant recovery was observed to be more prominent for ATRA‐treated rats as compared to the rats that were allowed to recover naturally for 56 days. Tissue arsenic deposition was significantly reduced in the uterus upon continuous ATRA treatment. The results revealed that ATRA reversed arsenic‐induced free radical generation, activated the anti‐oxidant defence system, and subsequently repressed p53‐dependent apoptosis through inhibition of the MAPK signaling components. J. Cell. Biochem. 118: 3796–3809, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Arsenic is a major pollutant leading to serious health hazards all over the world, including reproductive failures and cancer. Treating affected individuals with all ‐trans retinoic acid, a vitamin A derivative, can ameliorate the disruptive effects of arsenic. All ‐trans retinoic acid ameliorated arsenic‐induced ROS generation and restored redox balance, repressed p53‐dependent apoptosis of uterine cells, and modulated the MAPK signaling components, ERK and JNK.